(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Background: Staphylococcus aureus is a common cause of infection of the bloodstream in new borne, there is insufficient based on population’s evidence available. Objectives: This study aims to investigate the distribution of S aureus bacteremia in new borne. Materials and Methods: They conducted based on population’s surveillance of every S. aureus bacteremia as in neonates with blood culture-proven neonatal sepsis. Blood samples a prospective, cross-sectional study was carried out on from 80 different sources (newborns) have been utilized in the present study with blood culture-proven neonatal sepsis. They were collected from new borne that frequented hospital in Kirkuk City. They were categorized according to the age of onset of symptoms as having early-onset sepsis and late-onset sepsis. The bacterial profile that resulted from their blood cultures was analyzed. Results: This study included eighty clinical samples from new borne who visited the Kirkuk City hospital. Including 50 (62.5%) staphylococcus aureus detected on mannitol salt agar. While 20 (25%) isolate other bacterial spp. and 10 (12.5%) show no growth on blood agar. Each of the fifty S. aureus isolates appeared resistance to Augmentin, Tetracycline, Trimethoprim, and Azithromycin, where as 80% were responsive to Cefotaxime and Chloramphenicol. Conclusions: S aureus bacterial infections is a significant source of mortality in the pediatric population. Healthcare disorders and devices that are inserted pose major risks. Methicillin-resistant S. aureus has an extremely low rate of mortality.